Guidance Note for Staff on Undertaking Targeted (Risk-Based) Reports on the Observance of Standards and Codes (ROSCs) in Financial Regulation and Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
In September 2009, the International Monetary Fund (IMF) and the World Bank (WB) Boards approved changes to the Financial Sector Assessment Program (FSAP) to (i) make it more flexible and better-aligned with country needs as well as IMF and WB financial sector priorities and core responsibilities; (ii) enhance the quality, candor, and comparability of assessments; and (iii) better-integrate FSAP analysis into the institutions' evolving mandates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Assessment; Development Vice Presidency; PP; Rosc Update; Targeted Assessment